Continuum Damage Mechanics (CDM) modelling of dislocation creep in 9-12% Cr creep resistant steels - Stracey, Muhammad Ghalib (Centre for Materials Engineering, 2017)
The generation of electricity to meet an ever-growing demand has become a defining characteristic of the modern world for both developed and developing nations alike. This, coupled with the intensifying concern with pollution and its effects on the environment has put immense pressure on how quickly and efficiently power is produced. Being the most prevalent source of electricity generation, coal fired power plants have been subject to increasing scrutiny and study in an effort to improve the efficiency at which they operate. Hence, coal fired power plants are being run at increased temperatures and pressures such as those observed in Super-critical and Ultra-super-critical plants. This has by extension put excessive demand on materials used in these plants specifically within the boiler and superheater pipe sections where the most extreme thermodynamic conditions are experienced. The most commonly used materials for these applications are in the family of ferritic/martensitic 9-12% Cr steels chosen for their superior material properties especially during long-term exposure as coal fired power plants typically operate for over 20 years before being decommissioned. One of the lesser understood aspects of 9-12%Cr steels is with regard to their long-term material properties specifically that of creep degradation and deformation. This has been partially due to the reliance of creep life predictions in the past being based on accelerated creep testing and empirically based modelling. With the relatively recent revelations of empirically based modelling shown to be inaccurate when extrapolated to the long-term, a need has been identified amongst researchers to develop more accurate models based on physical relationships and material microstructure. Moreover, the insight obtained from modern experimental techniques and technologies as well as ever-expanding computing capabilities provide an opportunity to produce microstructurally based models with a high degree of complexity. Thus motivated, the focus of this dissertation was to develop a physically based dislocation creep model using the Continuum Damage Mechanics (CDM) approach. A dislocation CDM model was developed and implemented in the current work for uniaxial creep loading using the numerical modelling software Matlabᵀᴹ. The CDM approach was built upon fundamental dislocation theory as well as other microstructural considerations pertaining to dislocation creep including subgrain coarsening, M₂₃C₆ precipitate coarsening and stress redistribution. The CDM model was found to require calibration in order to be applied to specific 9- 12% Cr steels which was implemented using a parameter optimisation routine. The results obtained were compared with experimentally obtained, long-term creep-time and microstructural data for the 11% Cr steel CB8 and the 9% Cr steel P92. The CDM creep-time predictions were found to vary in accuracy depending upon the experimental data against which the model was calibrated. Upon further investigation, it was hypothesised that the discrepancy observed was due to the formation of the Modified Z-phase in some of the long term creep data but not in others which was based primarily on the differing creep exposure times of the various samples. The CDM creep-time predictions for P92 were found to be accurate when compared with experimental results regardless of creep exposure times. The apparent difference in the approximation of the creep deformation for the two steels was concluded as being due to the formation of the Modified Z-phase in CB8 but not in P92 as Modified Zphase formation is intrinsically linked with the Cr content of the steel.